Knowledge about Diabetic Foot Care is Related to the Ability to Care for Feet in People with Diabetes Mellitus - Yani Nurhayani; Titin Supriatin; Hani Ruh Dwi; Ruswati Ruswati; Marwati Marwati (Qualitative and Quantitative Research Center, 2022)
The most common complication in people with diabetes mellitus is diabetic foot problems. Efforts to prevent diabetic foot problems can be prevented with proper foot care. Checking the foot every day, whether there are wounds or bleeding, cleaning the foot every day, cutting nails, using comfortable shoes or slippers, and immediately contacting a doctor if the foot is injured. The purpose of this study identified the relationship between knowledge about diabetic foot care and the ability to care for the feet in people with diabetes mellitus. This study used a type of correlation research with a cross-sectional design. The subjects of this study were people with diabetes mellitus, who totaled 26 respondents. Data collection using questionnaires that are distributed to respondents. Univariate data analysis using frequency distribution and bivariate using chi-square. The result shows a relationship between knowledge about diabetic foot care and the ability to care for feet in people with diabetes mellitus. This research contributes to providing knowledge to people with diabetes mellitus. This knowledge contributes to motivating foot care activities to prevent diabetic foot injuries.